Multi‐institutional validation of a perfused robot‐assisted partial nephrectomy procedural simulation platform utilizing clinically relevant objective metrics of simulators (CROMS). (6th October 2020) - Ghazi, Ahmed; Melnyk, Rachel; Hung, Andrew J.; Collins, Justin; Ertefaie, Ashkan; Saba, Patrick; Gurung, Pratik; Frye, Thomas; Rashid, Hani; Wu, Guan; Mottrie, Alex; Costello, Tony; et al.
Abstract : Objective: To conduct a multi‐institutional validation of a high‐fidelity, perfused, inanimate, simulation platform for robot‐assisted partial nephrectomy (RAPN) using incorporated clinically relevant objective metrics of simulation (CROMS), applying modern validity standards. Materials and Methods: Using a combination of three‐dimensional (3D) printing and hydrogel casting, a RAPN model was developed from the computed tomography scan of a patient with a 4.2‐cm, upper‐pole renal tumour (RENAL nephrometry score 7×). 3D‐printed casts designed from the patient's imaging were used to fabricate and register hydrogel (polyvinyl alcohol) components of the kidney, including the vascular and pelvicalyceal systems. After mechanical and anatomical verification of the kidney phantom, it was surrounded by other relevant hydrogel organs and placed in a laparoscopic trainer. Twenty‐seven novice and 16 expert urologists, categorized according to caseload, from five academic institutions completed the simulation. Results: Clinically relevant objective metrics of simulators, operative complications, and objective performance ratings (Global Evaluative Assessment of Robotic Skills [GEARS]) were compared between groups using Wilcoxon rank‐sum (continuous variables) and parametric chi‐squared (categorical variables) tests. Pearson and point‐biserial correlation coefficients were used to correlate GEARS scores to each CROMS variable. Post‐simulation questionnaires were used to obtain subjective supplementation of realism ratings and training effectiveness. Results: Expert ratings demonstrated the model's superiority to other procedural simulations in replicating procedural steps, bleeding, tissue texture and appearance. A significant difference between groups was demonstrated in CROMS [console time ( P < 0.001), warm ischaemia time ( P < 0.001), estimated blood loss ( P < 0.001)] and GEARS ( P < 0.001). Six major intra‐operative complications occurred only in novice simulations. GEARS scores highly correlated with the CROMS. Conclusions: This perfused, procedural model offers an unprecedented realistic simulation platform, which incorporates objective, clinically relevant and procedure‐specific performance metrics.